Adult Higher Education in a Portuguese Prison - Moreira, J. António (2017)
Over the years, the European Union has strengthened measures that address the need to find answers to the challenges posed by the information society, which in turn underscores the importance of a focus on innovation of adult education, especially for those in conditions of social exclusion. The aim of this paper is to analyse the reality of Higher Education in Distance Learning and e-Learning in a prison context. The results from interviews, interpreted in a context of a non-positivist paradigm, show that students are rather motivated because they foresee a more attractive future if they have an academic diploma. Despite this, however, their expectations are not very high, because they acknowledge that their rehabilitation will be difficult due to the stigma of being an ex-prisoner. The results show, also, that the education process has many weaknesses and limitations mostly due to the lack